IMPLEMENTASI ARABIC BOWLINGUNTUK MENINGKATKAN KETRAMPILAN BERBICARA BAHASA ARAB DI MADRASAH ALIYAH - Zuzan Nabila Roichana; Afif Kholisun Nashoih (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Abstract The background of the research is the low learning achievement of students in learning Arabic, especially in speaking skills. Therefore, this study was directed to improve speaking skills through the use of the Arabic Bowling game in class XI MANPK Denanyar Jombang. This research is a descriptive qualitative research with classroom action research design which is taken through 2 cycles. Data was collected by 2 methods, namely observation and tests. Based on the research results, it is known that the implementation of Arabic Bowling at MANPK Denanyar Jombang is able to improve students' speaking skills. This is based on the evaluation carried out in the first cycle which reached an average of 72.9%, then increased in the second cycle which the evaluation value reached an average of 88.5%. In addition, the results of observations also state that the enthusiasm of students in participating in the learning process has increased, so that this has an effect on increasing student achievement, especially in speaking skills. Key Words: Arabic Bowling, speaking skills, Arabic language